Study of the cross sections for (γ,n)-reactions on р-nuclei 120Te, 136Cе in the giant E1 resonance energy region - V. M. Mazur; Z. M. Bigan; P. S. Derechkey; V. A. Zheltonozhsky; A. M. Savrasov (Ядерна фізика та енергетика)
Cross-sections of photonuclear reactions 120Te(γ,n)119Те, 136Се(γ,n)135Ce in the energy region of gamma quanta 9 - 18 MeV were studied. The measurements were carried out by activation technique. Experimental results were compared with the theoretical calculations carried out within the framework of the software package TALYS-1.9.